Impact of Visual Awareness of Postoperative Appearance on Functional Recovery After High Tibial Osteotomy: A Retrospective Case-Control Study - Bayrak, Hünkar Çağdaş; Karagöz, Bekir (The European Research Journal, 2026)
Objective: This study aimed to evaluate the impact of visual awareness of preoperative and postoperative leg appearance on patient satisfaction and functional recovery after medial open-wedge high tibial osteotomy (MOWHTO) in patients with varus malalignment. We hypothesized that providing patients with visual feedback of their cosmetic improvement may enhance perceived functional outcomes and overall satisfaction.Methods: A retrospective case-control study was conducted including 57 patients who underwent MOWHTO for varus malalignment between 2019 and 2023. Patients were divided into two groups: Group 1 (n=24), who were shown preoperative and postoperative leg photographs, and Group 2 (n=33), who were not. Functional outcomes were assessed using the Short Form-36 (SF-36) physical and mental scores and Lysholm score. Radiological parameters and joint range of motion were also evaluated preoperatively and at final follow-up.Results: Both groups showed significant postoperative improvements in SF-36 and Lysholm scores (P